2018
DOI: 10.3389/fphar.2018.00464
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 Mitigates Atherosclerosis Progression in Diabetic apoE–/– Mice by Skewing Macrophages to the M2 Phenotype

Abstract: Atherosclerosis (AS) in diabetic patients is often associated with low stability, which might be largely attributed to unfavorable macrophage polarization and increased inflammatory response induced by hyperglycaemia. Ginsenoside Rg3 is one of the main active principles of Panax Ginseng, which has been reported to be a natural ligand of peroxisome proliferator-activated receptor-gamma (PPARγ), a key nuclear transcriptional factor involved in inflammation and macrophage differentiation. However, it remains uncl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…In another study, Guo et al showed a similar observation [59]. Treatment of advanced glycation end products promoted the expression of M1 markers (iNOS and CD86) and pro-inflammatory molecules, whereas ginsenoside Rg3 reversed the M1 polarization to the M2 phenotype expressing arginase 1 and CD206 (i.e., mannose receptor), two M2 markers in vitro [59]. The administration of ginsenoside Rg3 promoted atherosclerotic plaque stability, which was accompanied by increased M2 phenotype macrophages and reduced M1 phenotype macrophages in the plaque [59].…”
Section: Ginsenosides In Pro-resolutionsupporting
confidence: 58%
See 3 more Smart Citations
“…In another study, Guo et al showed a similar observation [59]. Treatment of advanced glycation end products promoted the expression of M1 markers (iNOS and CD86) and pro-inflammatory molecules, whereas ginsenoside Rg3 reversed the M1 polarization to the M2 phenotype expressing arginase 1 and CD206 (i.e., mannose receptor), two M2 markers in vitro [59]. The administration of ginsenoside Rg3 promoted atherosclerotic plaque stability, which was accompanied by increased M2 phenotype macrophages and reduced M1 phenotype macrophages in the plaque [59].…”
Section: Ginsenosides In Pro-resolutionsupporting
confidence: 58%
“…In another study, Guo et al showed a similar observation [59]. Treatment of advanced glycation end products promoted the expression of M1 markers (iNOS and CD86) and pro-inflammatory molecules, whereas ginsenoside Rg3 reversed the M1 polarization to the M2 phenotype expressing arginase 1 and CD206 (i.e., mannose receptor), two M2 markers in vitro [59].…”
Section: Ginsenosides In Pro-resolutionmentioning
confidence: 84%
See 2 more Smart Citations
“…20(S)-Rg3 is a compound that has many biological effects of preventing ischemia-reperfusion injury, reducing oxygen free radicals, antioxidation, and inhibiting the activity of voltage-regulated pathways. Studies have reported that 20(S)-Rg3 as a nontraditional therapy has protective effects on diabetes itself, as well as diabetic cardiomyopathy, diabetic retinopathy, and atherosclerosis in DM [23,24]. Kang et al [20] reported 20(S)-Rg3 prevents the progression of renal damage and dysfunction in type 2 diabetic rats via inhibiting oxidative stress and advanced glycation end-product formation.…”
Section: Discussionmentioning
confidence: 99%